An Open for Replication Study: The Role of Feedback Timing in Synchronous Computer‐Mediated Communication. Issue 4 (9th July 2018) - Arroyo, Diana C.; Yilmaz, Yucel
Abstract : This study investigated the role of corrective feedback timing in the acquisition of Spanish noun–adjective gender agreement. Forty‐five learners completed a communicative task via synchronous computer‐mediated communication (SCMC) in one of three groups (immediate, delayed, control). The immediate‐feedback group received error reformulations immediately after their errors. The delayed‐feedback group did not receive feedback; however, at the end of the task, they were provided with an electronic document showing the errors they had made during the task with error reformulations. The control group performed the task without receiving feedback. The immediate‐feedback group outperformed the delayed‐feedback group in an oral production test, but there were no differences between the two feedback groups in a grammaticality judgment test. All study materials and data are made publicly available to encourage future replications. Open Practices: This article has been awarded Open Materials and Open Data badges. All materials and data are publicly accessible via the Open Science Framework athttps://osf.io/57zkv, the IRIS Repository athttps://www.iris-database.org, and Supporting Information accompanying this article. Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .